Introducing eHealth solutions in Slovenia to gain time for health education: a case of electronic patient appointment schedulin - Forstnerič, Sebastijan; Fijačko, Nino; Pajnkihar, Majda; Štiglic, Gregor (Nursing in the 21st Century, 2018)
INTRODUCING EHEALTH SOLUTIONS IN SLOVENIA TO GAIN TIME FOR HEALTH EDUCATION: A CASE OF ELECTRONIC PATIENT APPOINTMENT SCHEDULING Introduction. Accelerated computerization of health systems begun in Slovenia in 2008 with the eZdravje (eHealth) project. Various aspects of the system enable patients to track different aspects of their health care more efficiently. The eNaročanje (eScheduling) part enables patients to be more actively integrated into the health services, as well as presents significant help for administrative work and more time for health education. Aim. The aim of our research was to show which type of patient appointment scheduling is the least burdensome for nurses. Material and methods. We used a quantitative research methodology. Collecting data took place in May 2017. We gathered the various patterns of scheduling patients for appointments in a single month at an outpatient care unit in the north-eastern region of Slovenia. We collected the data concerning the time needed to perform different patients’ appointment scheduling and we interpreted the data with the help of descriptive statistics. Results and conclusion. Between January 2016 and January 2017 less than 1% of patients made appointments through eNaročanje. Since January 2017, when eNaročanje started in studied unit, the percentage of patients who made their appointments through eNaročanje increased, and by May 2017 there were 60 (20%) of the overall 298 patients in the study who used the system. We came to the conclusion that in the 17 workdays in May 2017 there were 126 (42%) appointments made by men and 172 (58%) by women. An average time spent personally or on the phone calls scheduling was significantly higher than the time spent through the eNaročanje service. We have shown that out of 17 workdays, the nurse spends more than an entire workday for the patient appointment scheduling tasks (8 hours, 13 minutes and 31 seconds). Information and communication based solutions can bring many advantages, especially regarding the time burden challenges that the nurses currently face, optimization of administrative work as well as promoting health care through education of patients.